Morphology and identification of the pupae of seven species of the genus Otiorhynchus Germar, 1822 (Coleoptera, Curculionidae, Otiorhynchini) - Gosik, Rafał; Sprick, Peter (Zootaxa, 2012)
The pupae of Otiorhynchus armadillo (Rossi, 1792), O. aurifer Boheman, 1843, O. crataegi Germar, 1824, O. meridionalis Gyllenhal, 1834, O. porcatus (Herbst, 1795) and O. salicicola Heyden, 1908, are described and illustrated for the first time. The pupa of O. sulcatus (Fabricius, 1775) is redescribed and illustrated. Characteristic features including chaetotaxy and habitus, measurements and a key to the species based on the pupae are also presented.